COMPARATIVE STUDY FOR SUBCHRONIC TOXICITY OF VASELINE OIL AND GLYCELAX - A. V. Voronkov; A. Yu. Terekhov; I. N. Dyakova; S. A. Kuleshova; N. S. Avramenko; E. E. Zatsepina; D. I. Pozdnyakov (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2016)
Contemporary therapeutic approaches offer a wide range of laxative agents, which are often used without a control, exceeding the regime recommended. Therefore, the comparative study for subchronic toxicity of both drugs from this group (Vaseline oil and Glycelax) appears interesting.The aim of the study was the comparison of a toxic influence of 14-days application of the drugs under study.Methods. The drugs were studied in two doses: higher therapeutic, and toxic, which 10 times exceeds therapeutic dose. We used "Polispektr-8/B" electrocardiograph, BC 2800vet (Mindray) hematologic veterinary analyzer, BS-380 (Mindray) biochemical analyzer, CL-50 urine analyzer. After the animals autopsy we determined organs' coefficient (heart, lungs, spleen, liver, stomach, kidneys, adrenals).Results. While studying the ECG of female rats, amplitude of R wave increased after they got Glycelax in both doses. Female rats who got Vaseline oil this index decreased at minimum dose and increased at maximum dose. After Glycelax application, male rats had an increased activity of alanine aminotransferase. After Vaseline oil application at maximum dose, female rats had alkaline phosphatase activity lowered. Female rats, which got a maximum dose of Vaseline oil had a total protein lowered. Glycelax at maximum dose increased the content of bilirubin and its fractions in male and female rats, while Vaseline oil application at maximum dose increased the content of bilirubin in female rats. Male rats which got Glycelax had hemoglobin and hematocrit level increased.Conclusion. At long-term application of Vaseline oil, animals of both genders had heart disorders with possible development of arrhythmia, hepatotoxic effect, lipid exchange dysfunction. After excessive use of Glycelax the above mentioned is added with possible hemoglobin and rheological blood properties level decrease.